The Influence of Income Level, Financial Literature, and Social Media Use on Teachers Consumption Behavior - Hidayati, Nur; Kartikowati, Sri; Gimin, Gimin (FKIP-Universitas Riau, 2021)
This study aims to identify and analyze the influence of income level, financial literacy, use of social media; on the consumptive behavior of teachers. The total population in this study was 127 civil servant teachers. The sampling technique used Isaac Michael's table with an error rate of 5%, the number of samples in this study was 94 teachers. The process of taking sample data using proportional random sampling technique. Data was obtained by using questionnaires and documentation methods. The collected data was then analyzed using descriptive analysis and multiple regression analysis. The findings in this study are that there is no significant effect of the income level variable on the consumptive behavior of teachers, there is a significant influence of the financial literacy variable and the use of social media on the consumptive behavior of PNS teachers. The level of consumptive behavior is related to the financial literacy of teachers and the use of social media. So that teachers are expected to increase their level of financial literacy and reduce the intensity in using social media to minimize consumptive behavior.